Impact of the Four Quality "Training, Service, Information System and Information" on the Use of Information System in an Information-Intensive Sector - Laila Zeroual; Zerouali Ouariti Ouafae; Outseki Jaouad (International Journal of Supply Chain Management, 2021)
Today, information is crucial and the flow of information is becoming more and more numerous, so their management is delicate, hence the need to use an information system that supports all production systems, and the majority of competitive advantages is achieved through the intelligent use of these information systems.It is in this context of disrupted information that the use of information systems is necessary in organizations, as they have greatly influenced the ways of work and management. For this purpose, they allow easy access to relevant information in quantity and in real time, the rapidity of analyzing this information and the possibilities for dissemination and exchange between the partners, without forgetting the possibilities for storage and archiving in a more secure way than human intervention could.The study examines the impact of quality of training, service quality, information system quality and information quality on the use of an information system. A quantitative study is conducted to test these effects, the findings of this research are mainly comprised by three facts: (1) the use of information systems is obligatory in the context of intensive information. (2) Voluntary or mandatory use status must be specified in the analysis, (3) there is no specific antecedent to the act of use of IS in the retail sector